THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE ON POTENTIAL FINANCIAL DISTRESS OF TECHNOLOGY COMPANIES ON THE INDONESIA STOCK EXCHANGE - Moh. Ma’ruf MY Tunggeng; Muhammad Yunus Kasim; Vitayanti Fattah; Suryadi Samudra (RADJA PUBLIKA, 2025)
This study aims to determine the effect of good corporate governance and financial performance on the potential for financial distress with company size as a control variable in technology companies on the Indonesian stock exchange for the 2021-2023 period. The type of data used is quantitative data sourced from secondary data. The population in this study are technology sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The technique used in this sampling is purposive sampling and 16 companies were obtained as samples in this study. The results showed that the variables of the Independent Board of Commissioners, ROE, and DER partially had no effect on the potential Financial Distress of Technology Companies on the Indonesia Stock Exchange for the period 2021-2023. Meanwhile, Company Size as a control variable partially has a significant effect on the potential Financial Distress of Technology Companies on the Indonesia Stock Exchange for the 2021-2023 period. Then, the variables of Independent Board of Commissioners, ROE, DER, and Company Size simultaneously have a significant effect on the potential Financial Distress of Technology Companies on the Indonesia Stock Exchange for the period 2021-2023.